PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DESA SUNGAI SEPETI KECAMATAN SEPONTI KABUPATEN KAYONG UTARA - Indrayani, Yuliati; sairi, agus; Wardenaar, Evy (Universitas Tanjungpura, 2024)
The purpose of this study is to record and describe the use of types of medicinal plants by the community in Sungai Sepeti Village, Seponti District, North Kayong Regency. The research was conducted in Sepeti River village for four weeks effectively in the field, start from August 15th